Quantifying the costs of hospital admission for families of children with a febrile illness in the North East of England - Marieke Emonts; Emma Lim; Rebecca Walsh; Fabian Johannes Stanislaus van der Velden; Holly Smith (BMJ Publishing Group, 2024)
Objective To assess the financial non-medical out-of-pocket costs of hospital admissions for children with a febrile illness.Design Single-centre survey-based study conducted between March and November 2022.Setting Tertiary level children's hospital in the North East of England.Participants Families of patients with febrile illness attending the paediatric emergency departmentMain outcome measures Non-medical out-of-pocket costs for the admission were estimated by participants including: transport, food and drinks, child care, miscellaneous costs and loss of earnings.Results 83 families completed the survey. 79 families (95.2%) reported non-medical out-of-pocket costs and 19 (22.9%) reported financial hardship following their child's admission.Total costs per day of admission were median £56.25 (IQR £32.10-157.25). The majority of families reported incurring transport (N=75) and food and drinks (N=71) costs.Conclusions A child's hospital admission for fever can incur significant financial costs for their family. One in five participating families reported financial hardship following their child's admission. Self-employed and single parents were disadvantaged by unplanned hospital admissions and at an increased risk of financial hardship. Local hospital policies should be improved to support families in the current financial climate.